Measuring the Political Power of Indonesian Democratic Party of Struggle (Case Study of Megawati's Leadership Style) - Aharits Saputra; Faisal Fasa Rahmatulah; Ighna Karimah Nurnajah; Karina Maulita Firdaus; M Fikri Fahrizal (GoResearch - Research & Publishing House, 2023)
This paper aims to analyze what factors make PDIP successful become the largest and most powerful party in Indonesia. There are several analyzes that we can do discussed comprehensively, including how the history of the birth of Indonesian Democratic Party of Struggle (PDIP) and what the ideology of the party, what kind of strategy was built by PDIP and what was the last one impact of the current PDIP power. Types of research this is a descriptive qualitative research with our technique of collecting data and facts using the library research method (library reasearch) it is considered sufficient accurate in discussing the political power of PDIP in Indonesia. The History of the Formation of the Party Pdip (1973-Present). The results of the discussion in this paper arewith a political strategy presenting figure or political positioning with the political actor Megawati as the actor The most influential in PDIP is what PDIP is doing, from history to strategy its politics can make PDIP a strong party in Indonesian politics, no we can deny that PDIP succeeded in attracting the sympathy of the people with everything the advantages. and PDIP is able to position itself when it becomes the opposition or when it is serve as the current government.